ORE-BEARING GABBROID ROCKS OF THE SMELYY ANORTHOSITE PLUTON - Borisenko L.F.; Tarasenko V.S.; Kolomiyets G.D.; Lukinykh A.D. (My University, 1989)
Ore-bearing gabbroid rocks were recently detected in various places on the Ukrainian shield as segregations relatively high in ilmenite and locally in apatite. The ore body in gabbro-norite of the Smelyy anorthosite pluton studied by us in relatively high in TiO2. Because this pluton is part of the Korsun'-Novomirgorod batholith, the latter can be regarded as a potential source of titanium mineralization. Thus, the detection of ilmenite ore in the Smelyy pluton confirms the accuracy of conclusions that the Ukrainian shield is one of the main titanium provinces in the USSR.